SOSIALISASI DAN PELATIHAN PENANGANAN CEDERA BAGI PELATIH SEPAK BOLA LISENSI D TINGKAT JAWA TIMUR - Shinta Arisanti; Florence Pribadi; Azyvati Karesna Putera; Amadea Arum Natasha; Bachtiar Rizki Nardiansyah (JPM PAMBUDI, 2022)
Injuries to sports activities can have a negative impact on physical activities. Sports injuries include physical injuries that usually occur during physical activity, whether amateur or professional. Football is a type of sport that has a high intensity and requires good physical endurance. This sport is very susceptible to injury. First aid training in the form of handling injuries can be seen as an important skill for the formation and training of needed experts, in this case trainers. The purpose of first aid techniques in the form of handling injuries are as follows; protect the further life of the individual, prevent adverse injury situations, and recover in the form of rehabilitation. The activity was carried out on February 16, 2022 at the Kampi Hotel Surabaya. The number of participants who took part in this community service activity was 73 football coaches, members of PSSI East Java.